Wildfire and Family Forest Owners: Concern, Advice, and Wildfire Reduction Behaviors from the United States National Woodland Owner Survey - Sarah M Butler; Brett J Butler; Emma M Sass (Forest Science, 2024)
Extreme wildfire is an increasing threat to lives, property, and ecosystems across the United States and many parts of the world. Family forest owners (FFOs) own a large percentage of forestland in the United States, and actions and behaviors on their forestland have a large impact on wildfire prevention and mitigation across the landscape. Using data from the USDA Forest Service’s 2018 National Woodland Owner Survey, we investigated national and regional FFO wildfire attitudes and behaviors. We see that concern for wildfire is relatively high across the United States; however, this concern does not always lead to wildfire reduction activities on the landscape. There is some variation among regions, with concern about wildfire and past wildfire reduction activities highest in the western US (76% and 37%, respectively), followed by the South (63% and 11%, respectively), and lowest in the northern region (50% and 8%, respectively). Understanding these aspects of wildfire and FFOs on a national level provides a broader context for the more focused studies across the country and acts as a launch point for more in-depth research in the future. Study Implications: This study assesses family forest owner (FFO) wildfire concern, information needs, and action, both past and intended, at national and regional levels across the United States. As wildfire is predicted to increase in frequency and severity into the future due to climate change, this research provides a reference line and a launch point for future studies. Understanding current concern levels and landowner characteristics can inform programs and policies aimed at mitigating severe wildfires. For example, the disconnect between concerns and actions can be used as an entry point for motivating additional owners to take steps towards active management. Concentrating efforts in fire-prone areas is important, but seeing that wildfire is a concern of family forest owners across much of the country suggests that this can be an important issue for starting conversations with many owners and possibly increasing their engagement with conservation efforts.